Effect of low-carbohydrate diet on adiponectin level in adults: a systematic review and dose-response meta-analysis of randomized controlled trials. Issue 14 (6th August 2022) - Shemirani, Farnoosh; Golzarand, Mahdieh; Salari-Moghaddam, Asma; Mahmoudi, Maryam
Abstract: Background: To the best of our knowledge, no previous study has reported findings on the effects of low-carbohydrate diet (LCD) on adiponectin concentration. Objective: The current systematic review and dose-response meta-analysis was carried out to systematically review the available controlled clinical trials about the effect of LCD on adiponectin level in adults. Methods: Literature searches of PubMed/Medline, Scopus and Web of Sciences were conducted up to August 2019. Randomized controlled trials (RCTs) which assessed the effect of LCD on the adiponectin level were selected. Results: Eleven studies, including 1047 participants (LCD = 534 and control = 513), were included in the meta-analysis. Proportion of carbohydrate from calorie was from 4 to 34%. Time of the follow-up varied between studies and ranged from 6 to 152 weeks. LCD intake mildly but significantly increased adiponectin (0.02 µg/ml, 95% CI: 0.01 to 0.03, P  < 0.001). Dose-response analysis indicated a nonlinear association between the percentage of carbohydrate and change in adiponectin level from baseline ( P  = 0.04). After subgroup analysis based on the proportion of carbohydrate from calorie, there was a significant increase in adiponectin concentration in studies that prescribed <30% of calorie from carbohydrates (0.12 µg/ml, 95% CI: 0.07–0.18). In contrast, diets which consisted ≥30% of carbohydrates had no significant effect on adiponectin (0.50 µg/ml, 95% CI: −0.46 to 1.48). Also, meta-regression analysis revealed that age ( β  = 0.04, P  = 0.15), baseline BMI ( β = −0.15, P  = 0.15), time of follow-up ( β  = 0.01, P  = 0.17), percentage of carbohydrates ( β  = 0.004, P  = 0.90), percentage of protein ( β = −0.12, P  = 0.08), percentage of fat ( β  = 0.20, P  = 0.61) and baseline adiponectin ( β  = 0.001, P  = 0.97) are not sources of heterogeneity. Conclusion: This systematic review and meta-analysis demonstrated a mild but significant effect of LCD on adiponectin concentration compared to control groups.